2001
DOI: 10.1056/nejmoa010692
|View full text |Cite
|
Sign up to set email alerts
|

Transient Intestinal Carriage after Ingestion of Antibiotic-ResistantEnterococcus faeciumfrom Chicken and Pork

Abstract: The ingestion of resistant E. faecium of animal origin leads to detectable concentrations of the resistant strain in stools for up to 14 days after ingestion. The organisms survive gastric passage and multiply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 20 publications
3
105
0
3
Order By: Relevance
“…The authors therefore suggested either a mutual spread of resistant enterococci between humans and pigs, or the existence of a common reservoir of resistant enterococci. The hypothesis that animals can be a source of resistant enterococci for humans could be supported by the findings of Sorensen et al [65]. In the latter study, the survival of animal derived enterococcal strains in the human intestine was investigated in 18 volunteers.…”
Section: Transmission Of Tetracycline and Mls Resistancementioning
confidence: 86%
“…The authors therefore suggested either a mutual spread of resistant enterococci between humans and pigs, or the existence of a common reservoir of resistant enterococci. The hypothesis that animals can be a source of resistant enterococci for humans could be supported by the findings of Sorensen et al [65]. In the latter study, the survival of animal derived enterococcal strains in the human intestine was investigated in 18 volunteers.…”
Section: Transmission Of Tetracycline and Mls Resistancementioning
confidence: 86%
“…Frequent empirical-based antibiotic therapy of humans, the addition of antibiotics as growth promotants in livestock feed, and antibiotic misuse have been implicated in the selective proliferation of resistant strains (Pantosti et al, 1999;Del Grosso et al, 2000;Mateu and Martin, 2001;O'Brien, 2002;Hershberger et al, 2005). The transmission of antimicrobial-resistant strains of pathogenic bacteria to humans is of increasing significance (Sørensen et al, 2001;Kuehn, 2007). In addition to direct colonization, public health costs include reduced efficacy of empirical antibiotic use, reduced choices for treatment, and possible coselection of virulence traits among pathogens (Mølbak, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…in nosocomial infections, many have suggested that the hospital setting serves as the reservoir for antimicrobial-resistant strains (Ruiz-Garbajosa et al, 2006). Additional studies suggest environmental sources of the bacteria, including animals, can serve as important reservoirs for antimicrobialresistant Enterococcus strains (Sørensen et al, 2001;Mallon et al, 2002). Studies have demonstrated a link between human sources of resistant strains of Enterococcus isolates and the environment, and have suggested that animals and their products are contaminated secondary to interaction with humans and the environment (Aarestrup et al, 1995;Iversen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest has been the potential for foods as a vehicle for transmission of these strains to humans or, alternatively, as a reservoir for horizontal transfer between strains. This might be considered credible since once ingested, enterococci can survive gastric passage, multiply, and colonize the gastrointestinal tract for a significant amount of time (24). Indeed, there is strong epidemiological evidence to link the use of antibiotics in human medicine and animal agriculture with the presence of resistant strains in animal products.…”
mentioning
confidence: 99%